Academic Procrastination of Guidance and Counseling Students - Yenni Rizal; Kamaruzzaman Kamaruzzaman; Uray Herlina; Melina Lestari (STAI Hubbulwathan Duri, 2023)
This study aims to determine the level of student academic procrastination after the Covid 19 pandemic. This research uses a quantitative approach with a descriptive method. The participants involved in this study were 150 students of the Guidance and Counseling study program at the 2021 Academic Year of the 2021 PGRI Pontianak Teachers' Training College. The sample technique used was saturated sampling because it used the entire population as a sample. The data collection tool used in this study was the modified Tucman scale of academic procrastination scale. The descriptive data analysis used was to divide the number of participants in each interpretation category (ni) by the total number of participants (n) and then the results were multiplied by 100. The results of this study indicate that in general the description of the level of academic procrastination of students of the Guidance and Counseling Study Program IKIP PGRI Pontianak category